Aplicação de uma metodologia para entrada em novos mercados internacionais com abordagem ecológica - Fiedler, Larissa Favero (My University, 2019)
The growing demand for products with a sustainable approach brings companies the challenge of making adjustments to meet these preferences. This challenge is even greater at the international level, as each country has its own laws and regulations, as well as different consumer behaviors for ecologically correct products. In this sense, the overall objective of this study is to apply a methodology for the strategic decision to enter into a new international ecological market based on the model of Gurău and Ranchhod (2005). Therefore, a theoretical knowledge was sought, in the areas of sustainability and internationalization of companies with an ecological focus, searching for authors that related these areas and who proposed a model that can be tested in order to help companies to enter foreign sustainable markets. For the execution of the research, the qualitative study method with exploratory approach was used, being a case study when testing the chosen model in a company that has ecological character. Thus, an interview was conducted with the chosen company to define, among other aspects, the destination country of interest of the company, Portugal. Afterwards, the data collection was performed, through research on official company pages, databases and official reports. The research results show that, according to the model studied, the chosen market is not attractive due to the high costs of adaptation and potential low profitability. However, the demand for juices and sustainable products exists in Portugal and the private labels have gained more space in this market. In order for the internationalization of the company with an ecological focus to be viable in Portugal, it will be necessary to make some previous adaptations in terms of ecological standards, packaging, labels, marketing and advertising (sic).
A crescente demanda por produtos intitulados sustentáveis traz às empresas o desafio de realizar adequações para atender essas expectativas. Tal desafio se mostra ainda maior no âmbito internacional, já que cada país possui suas próprias leis e regulamentos, além de diferentes preferências dos consumidores por produtos ecologicamente corretos. Nesse sentido, o objetivo geral desse estudo é aplicar uma metodologia para a decisão estratégica ao entrar em novo mercado internacional ecológico, com base no modelo de Gurău e Ranchhod (2005). Para tanto, buscou-se conhecimento teórico nas áreas de sustentabilidade e internacionalização de empresas com enfoque ecológico. Os autores pesquisados criaram relações entre essas áreas, e propuseram um modelo que pode ser testado de forma a auxiliar empresas a adentrarem mercados externos sustentáveis. Para a execução da pesquisa, utilizou-se o método de estudo qualitativo com abordagem exploratória, sendo realizado o estudo de caso ao testar o modelo escolhido em uma empresa que possui caráter ecológico. Assim, foi realizada uma entrevista com a empresa escolhida para definir, entre outros aspectos, o país de destino de interesse da empresa, Portugal. Após, a coleta de dados foi realizada por meio de pesquisa em páginas oficiais de empresas, bancos de dados e relatórios oficiais. Os resultados da pesquisa evidenciam que, segundo o modelo estudado, o mercado escolhido não é atrativo devido aos altos custos de adaptação e potencial baixa lucratividade. Todavia, a demanda por sucos e produtos ecológicos é existente em Portugal e as marcas próprias têm ganhado mais espaço nesse mercado. Para que a internacionalização da empresa com enfoque ecológico seja viável em Portugal, será necessário realizar algumas adaptações prévias em termos de padrões ecológicos, embalagem, rótulos, marketing e publicidade (sic).
Keywords: Sustentabilidade; Marketing de exportação; Marketing